Magnetorheological Polishing Based on Honing Vertical Mechanism for Inner Surface of Titanium Alloy Pipes - Wanli Song; Zhen Yang; Dezhi Meng; Na Wang; Seung-Bok Choi (Lubricants, 2024)
Recently, high internal surfaces for titanium alloy pipes have been required due to the increment of various applications such as aerospace components. In this work, vertical magnetorheological polishing (VMRP) is carried out to achieve high polishing performance on the internal surface of the titanium alloy pipe. A series of comparative experiments were conducted to investigate the polishing mechanism of magnetorheological polishing (MRP) fluid and enhance the polishing performance. It is shown from the experimental results that the VMRP method under the opposite polarity arrangement improves the surface roughness from 47.85% to 83.34% by reducing unwanted vibration and noise during operation. This provides nanoscale surface polishing quality, while such a precision cannot be achieved from the previous horizontal MR polishing apparatus method. It is found that under a 2700 cycle polishing time, a polishing process combining a rough and fine polishing approach with a combination of different particle diameters results in an axial surface roughness of 0.05 μm and circumferential surface roughness of 0.038 μm, respectively. It is also identified that the axial surface roughness of 0.04 μm–0.041 μm is achieved through the combination of high- and low-speed polishing process after 1602 cycles.